Impacts of Invasive Species on Commercial Forest Plantations in Africa Context: A Review - publisher, publisher; Ole Kiyiapi L., James (African Journal of Education,Science and Technology (AJEST), 2022)
Planting forests with non-native or exotic species are increasing worldwide as the demand for forest product, ecosystems and environmental benefits continue to grow. Characteristic life-history traits such as simple establishment, speedy growth, high propagule pressure, and low shade tolerance render the exotic trees better alternatives in commercial forest establishment. Several exotic tree species in forests now feature notably on the lists of invasive alien plants in many parts of the world and require to be sustainably managed to provide opportunities that enhance economic development. However, the consequence of exotic invasive species in commercial forestry remains largely fragmented in development and management. This paper, therefore, attempts to collate this information by looking at the status of exotic invasive species in commercial forests, their beneficial aspects and threats in commercial forestry. Management of exotic invasive species through a review of 126 papers from secondary sources discussing invasive species and their consequences on commercial forests are also explored. The overall impact is huge economic and ecological loss. The knowledge is useful to predict problems in other regions of the world with the same species and to guide research or management actions on other problematic but less studied tree species.